Preliminary Study on the Skin Lightening Practice and Health Symptoms among Female Students in Malaysia - Rusmadi, Siti Zulaikha (J Environ Public Health, 2015)
Many cases of dermatologic complication were reported with the use of skin lightening products. This study assessed the skin lightening practice and health symptoms among female students. Self-administered questionnaire was distributed to 104 female students (56 undergraduates and 48 postgraduates) aged 24 ± 2 years in Universiti Putra Malaysia. A total of 60.6% (N = 63) of the female students used skin lightening products (61.9% of undergraduates and 38.1% of postgraduates). Reasonable price (N = 35, 55.6%) and ingredients (N = 29, 46%) were considered the most important factors in the product selection. Most respondents purchased the product from drugstores (N = 39, 61.9%). Twenty-two respondents (34.9%) in this study experienced skin problem from the products they used. Skin peeling (N = 13, 12.5%) and acne (N = 9, 8.7%) were the most frequent symptoms experienced. Most of the respondents have the perception that lighter skin provides high self-esteem (N = 56, 53.8%) and looks beautiful and healthier (N = 54, 51.9%). The use of skin lightening products is common among female students in this study and some of these products can cause skin problems such as skin peeling, acne, and itching.